ZCE 538/2 - Radiobiology and Radiation Chemistry [Radiobiologi dan Kintia Sinaran] - February - March 2005 - PPSF, Pusat Pengajian Sains Fizik (2005)
UNIVERSITI SAINS MALAYSIA Second Semester Examination Academic Session 2004/2005 February - March 2005 ZCE 538/2 - Radiobiology and Radiation Chemistry [Radiobiologi dan Kintia Sinaran] Duration: 2 hours [Masa : 2 jam ]